Brief observation of five generations of China’s leaders - Batpenova, Z. S.; Daulet, F.; Shaimerdenova, G. (Journal of Oriental Studies, 2016)
This article is a brief review of five generations of political leaders in China. The article describes the history of the development of the political system and the results of the country’s leadership during the governance of each generation of China’s leaders, starting with the first generation, which is represented by Mao Zedong and completing with Xi Jinping, who is the head of the country right now.